Teachers’ Competence and the Performance of Grade 9 Technology and Livelihood Education Students in Achieving Most Essential Learning Competencies (MELCs) - Aquino, Mary Ann (Journal of Interdisciplinary Perspectives, 2025)
This research study was conducted to determine TLE teachers' level of competence and the performance of Grade 9 in achieving MELCs in Cookery in District V of the Schools Division of Quezon City. Significant relationships between these two variables were also tested. The descriptive-correlational study involved randomly selected 283 Grade 9 students during the School Year 2022-2023. Simple Random Sampling Probability Method was also used in the study. The data was gathered through a questionnaire and analyzed using Weighted mean and Spearman's rank correlation coefficient. The researcher concluded that TLE teachers demonstrate strong competence in helping the students learn, know, and understand what their teacher teaches, becoming better teachers every day, and engaging the community. Likely, students demonstrate a significant improvement in knowledge, skills, and attitude in MELCs in Cookery. In addition, there is a significant relationship between TLE teachers' competence and students' MELCs in Cookery regarding knowledge, skills, and attitude. It was recommended that teachers attend professional development training to enhance their competence and increase students' performance. They may also establish stronger engagement with the community to improve the MELCs in Cookery by collaborating with parents and guardians who can help when students are applying what they have learned from the school to their respective homes. Moreover, students may attend TESDA-initiated, school-initiated, and self-initiated training on Cookery that would enhance their skills, particularly in labeling food according to industry standards, preparing and presenting salads and dressings attractively, and packing food items in compliance with occupational health and safety procedures.